Portuguese Consensus and Recommendations for Acquired Coagulopathic Bleeding Management (CCBM). (16th April 2021) - Gomes, Manuela; Rodrigues, Anabela; Carrilho, Alexandre; Aguiar, José; Gonçalves, Luciana; Fernandez-Llimos, Fernando; Duarte-Ramos, Filipa; Rodrigues, Joana
We aimed to determine how Portuguese physicians handle major bleeding. We also aim to establish global diagnostic and therapeutic recommendations to be followed in clinical practice by using a step-wise approach of evidence generation. This study followed a three-step process: a steering committee desk review, a Delphi technique, an expert panel meeting. A modified 3-round Delphi including 31 statements was performed. Questions were answered in a five-point Likert-type scale. Consensus threshold was established as a percentage of agreement among participants ≥90% in the first round, and ≥85% in the second and third rounds. The level of consensus achieved by panelists was discussed with the scientific committee (January-2020). Fifty-one physicians participated in the study (compliance rate >90%). Analyzing the three rounds, consensus was reached on 20 items (64.5%) in the first, 4/11 items (36.4%) in the second and 6/7 items (85.7%) in the third. One statement about administration of clotting factor concentrates for bleeding control did not reach consensus. A high level of consensus was reached toward the need for implementing Patient Blood Management strategies in Portuguese hospitals, reduce exposure to allogeneic blood components, to use goal directed therapies for acquired bleeding management, and the need for evaluating blood transfusion indirect costs. A final version with 12 recommendations was built, according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Our results provide critically appraised and updated evidence on bleeding coagulopathies management in Portugal. Additional studies, mainly about indirect costs of blood transfusion, are needed.